2012
DOI: 10.1111/j.1551-2916.2012.05074.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pseudo‐Ion Approach in Classical MD Simulation: A Case Study on (U0.8Pu0.2)O2 Mixed Oxide

Abstract: In the present study a novel pseudo-ion concept is introduced in the context of classical molecular dynamics simulation. It has been shown here that this approach can successfully predict the thermo-physical and thermo-mechanical properties of solid solution of two isostructural compounds. (U 0.8 Pu 0.2 )O 2 mixed oxide is taken as the model system to demonstrate the proposed model. Various physical properties of (U 0.8 Pu 0.2 )O 2 has been calculated which match the experimentally obtained data reasonably wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…There exists two main families of potentials. One that considers U and Pu cations as one single entity and hence they include only three set of parameters (A-A, A-O, and O-O) but depends on the relative percentage of Pu in the MOX [17]. The second one treats explicitly the U and Pu cations.…”
Section: Introductionmentioning
confidence: 99%
“…There exists two main families of potentials. One that considers U and Pu cations as one single entity and hence they include only three set of parameters (A-A, A-O, and O-O) but depends on the relative percentage of Pu in the MOX [17]. The second one treats explicitly the U and Pu cations.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, these parameters are easily calculated by the lattice statics method with semi-empirical interaction potentials, or by ab initio methods. But despite successes of these methods, the analysis of the published data shows that calculated formation energies of a Schottky defect with different interaction potentials for uranium dioxide (8)(9)(10)(11)(12)(13)(14)(15) eV [6,7], as well as ab initio calculations (7.6-10.6) eV [8,9] systematically overestimate experimental values of the formation energy equal to (6-7) eV [3]. Calculated migration energies of cations systematically overestimate experimental values as well.…”
Section: Introductionmentioning
confidence: 93%
“…In general it should be noted, that, despite the successes of ab initio methods, they lead to significantly overestimated values of the lattice parameter and melting temperature in comparison with the experimental data. For the investigation of the mixed uraniumplutonium fuel authors in [13] proposed an approach where U and Pu cations are replaced by some pseudo-cation X, and the system of XO 2 with the fluorite-type structure is simulated. Potentials for this binary system are fitted to experimental data of the (U 0.8 Pu 0.2 )O 2 system.…”
Section: Simulation Technique and Interaction Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This class of potentials typically consists in three contributions: Coulomb interactions, core repulsions, and van der Waals dispersion [11], [12]. In the literature, several authors have proposed potentials based on the Buckingham form [13], [14] whilst some others improve it with the Morse form [15], [16] which is applied only to cation-anion pairs. Comparing several such pair potentials, Govers et al [17], [18] have shown that while a specific potential may well reproduce a subset of thermomechanical properties, none are able to reproduce an extensive set of properties.…”
Section: Introductionmentioning
confidence: 99%